PROBLATIKA GURU DALAM PENGGUNAN GOOGLE CLASSROOM SEBAGAI SARANA PEMBELAJARAN DARING PADA MATA PELAJARAN SEJARAH - Khuzil Afwan; Ika Rahmatika Chalimi; Astrini Eka Putri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
This study aims to determine the problems of teachers in the use of Google Classroom as a means of online learning in class X history subjects at SMKN 1 Pontianak. This research is a descriptive qualitative research with a case study approach. Data collection techniques used are observation, interviews and documentation. The results of the study show that the problems that occur during the online learning process by using Google Classroom as a learning tool, (1) the problems of teachers during online learning activities arise from the disturbance of the google classroom which often errors, quota constraints / inadequate signals, there are students who do not understand the material delivered online, the teacher cannot understand and recognize the character of the students because they do not know each other and there are students who do not participate in online learning activities. (2) the efforts of the teacher and the teacher's school to make it easier for students by not burdening them with heavy tasks, the school provides guidance for every student who has problems participating in online learning activities. In addition, the teacher provides motivation in every provision of material and assignments to be more active in learning and reading through the whatsups group, the teacher's efforts to always monitor and record all students whether they participate in learning activities or not through google classroom, students' efforts to find out what students do not understand from learning materials through Google and YouTube and books and other sources.